2016
DOI: 10.1017/jfm.2016.381
|View full text |Cite
|
Sign up to set email alerts
|

Controlling droplet bouncing and coalescence with surfactant

Abstract: The collision between aqueous drops in air typically leads to coalescence after impact. Rebounding of the droplets with similar sizes at atmospheric conditions is not generated, unless with significantly large pressure or high impact parameters exhibiting near-grazing collision. Here we demonstrate experimentally the creation of a non-coalescent regime through addition of a small amount of water-soluble surfactant. We perform a direct simulation to account for the continuum and short-range flow dynamics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 60 publications
2
28
2
1
Order By: Relevance
“…In this chapter, we will first benchmark our method performing the most commonly used tests, which include also a vis-a-vis comparison against previous experimental results [13,24,28,29,40,47,70,73]. Then we will examine on a qualitative basis the performances of the method on a fully turbulent, surfactant-laden multiphase flow.…”
Section: Resultsmentioning
confidence: 99%
“…In this chapter, we will first benchmark our method performing the most commonly used tests, which include also a vis-a-vis comparison against previous experimental results [13,24,28,29,40,47,70,73]. Then we will examine on a qualitative basis the performances of the method on a fully turbulent, surfactant-laden multiphase flow.…”
Section: Resultsmentioning
confidence: 99%
“…By adding surfactants or contaminants, droplet collision modes can be controlled. In particular, mode maps and characteristics of collisions of liquid droplets with surfactants or contaminants are given in [41]. Since, in real technologies, the presence of various impurities in the droplets is possible, and their concentration may change during the process (for example, due to evaporation or burnout), it is further advisable to study the processes of collisions of liquid droplets in an aerosol with the addition of surfactants or contaminants.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
“…For binary Newtonian droplet collisions, the current studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] are mainly focused on two aspects: from binary low-viscosity droplet collisions to binary high-viscosity droplet collisions, and from binary homogeneous-droplet collisions to binary heterogeneous-droplet collisions. Jiang et al [9] and reflexive separation of droplets were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the capillary instability and an energy balance, a scaling law for the evolution of the threshold impact velocity was established for head-on collisions. The research of Pan et al [17] identified the key mechanisms governing the impact dynamics of surfactant-coated droplets in the air and imply the potential of using a small amount of surfactant to manipulate impact outcomes. Compared to the Newtonian liquids, relatively few studies [24][25][26][27][28][29][30] have been conducted for the non-Newtonian liquids, which are of relevance to, for example, polymers.…”
mentioning
confidence: 99%